Parque industrial – ciclo productivo sostenible (2021)
The water elements that Bogotá has are a fundamental part of the growth of the city as elements that help its development, but they have been affected for the same reason, the excessive growth of the population has generated great pollution to these and apart from this the non-regularization of industrial zones has significantly affected these hydric elements. It is because of the above that the present research aims to develop the city and the industry (Specifically the refrigerator industry of the southern highway with Boyacá Avenue) in an efficient, sustainable and sustainable way, through urban renewal and establishing mechanisms to generate a production cycle that does not affect the water element in such an aggressive way, also establishing public space for people to appropriate and make the river part of their environment.